Answer:
b= -10
Step-by-step explanation:
9^ -8 * 9^ -2
We know that a^b * a^c = a^ (b+c)
9^ (-8+-2)
9^ -10
We want it in the form a^b
a=9
b= -10
Answer:
974
Step-by-step explanation:
(91.01)*(10.7)
91.01*(10.7)
91.01*10.7
973.80700
974
Answer:
c
Step-by-step explanation:
1.58 times the number of n bags equal to z money nedded to buy n bags of popcorn
Answer:
d = 4
Step-by-step explanation:
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Given a₁ = - 2 and a₈ = 26 , then
- 2 + 7d = 26 ( add 2 to both sides (
7d = 28 ( divide both sides by 7 )
d = 4